Mathemagic or Mathetragic : A Thematic Analysis of Student-reported Antecedents of Academic Emotions in Middle-school Mathematics - Madtha, Samuel Antony (2021)
Understanding students’ academic emotions and their influencers and implications has been a challenge and growing interest in educational research (Martínez-Sierra & García-González, 2014; Larkin & Jorgensen, 2015; etc.). The purpose of this qualitative study is to examine positive, negative and mixed emotional experiences involved in general, non-test engagement with mathematics towards understanding the variety and dynamics of emotions and their antecedents. The data collected comprised of reflections on emotional experiences associated with math-learning and achievement maintained in journals by thirty middle-school students from Delhi, India. Thematic analysis of the data led to the identification of three main categories of emotion-influencing factors and of the collective and mitigating influences of key antecedents across the three categories: lesson planning and implementation, classroom culture and expectations, and cognition and motivation. The findings are consistent with the Control-Value Theory of Achievement Emotions (Pekrun, 2006) and offer insights on classroom practices, conditions and environment that are likely to foster emotions that enhance math-learning and outcomes. The central message of the conclusion is that an overall positively perceived experience can be created by mitigating negative influences through an understanding of the collective contribution of antecedents towards the nature of emotional experiences.